2022
DOI: 10.2337/db20-1245
|View full text |Cite
|
Sign up to set email alerts
|

Topical Aspirin Administration Improves Cutaneous Wound Healing in Diabetic Mice Through a Phenotypic Switch of Wound Macrophages Toward an Anti-inflammatory and Proresolutive Profile Characterized by LXA4 Release

Abstract: Diabetic patients present a persistent inflammatory process, leading to impaired wound healing. Since non-healing diabetic wounds management shows limited results, the introduction of advanced therapies targeting and correcting the inflammatory status of macrophages in chronic wounds could be an effective therapeutic strategy to stop the sustained inflammation and to return to healing state. Here, we demonstrated in an excisional skin injury in diet-induced diabesity murine model that topic low-dose Aspirin (3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The topical application of low-dose aspirin can expedite wound healing by promoting the release of LXA4 from macrophages. 74 The removal of microglia, rather than circulating monocytes, hindered the postoperative decrease in circulating LXA4 levels, thus preventing neuroinflammation and memory impairment. 75 WRW4, a well-established and highly selective inhibitor of ALX/ FPR2, 12 counteracts the effects of LXA4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topical application of low-dose aspirin can expedite wound healing by promoting the release of LXA4 from macrophages. 74 The removal of microglia, rather than circulating monocytes, hindered the postoperative decrease in circulating LXA4 levels, thus preventing neuroinflammation and memory impairment. 75 WRW4, a well-established and highly selective inhibitor of ALX/ FPR2, 12 counteracts the effects of LXA4.…”
Section: Discussionmentioning
confidence: 99%
“…LXA4 is hypothesized to be a critical metabolite that facilitates various anti‐inflammatory mechanisms. The topical application of low‐dose aspirin can expedite wound healing by promoting the release of LXA4 from macrophages 74 . The removal of microglia, rather than circulating monocytes, hindered the postoperative decrease in circulating LXA4 levels, thus preventing neuroinflammation and memory impairment 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous complications associated with diabetes, diabetic foot is highly prevalent and serious 4 . It results from neuropathy and vascular lesions caused by lower extremity tissue damage, which can lead to ulceration, infection, tissue necrosis, and even amputation 5,6 . Studies have indicated that hyperglycaemia plays a pivotal role in the development of microvascular diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of lipid metabolism could render immunosuppressive microenvironment for the progression of lymphoma. In fact, the lipid metabolites, i.e., the arachidonic acid metabolites which are the major products of 12/15-lipoxygenases (ALOX15), have been turned out to be an important regulator of macrophage function [ 29 ]. ALOX15 exists in different mammalian isoenzymes designated together as 12/15-lipoxygenases since they have variable positional specificity to catalyze oxygenation at the 15-position and the 12-position of arachidonic acid.…”
Section: Introductionmentioning
confidence: 99%